2020
DOI: 10.3390/plasma3040016
|View full text |Cite
|
Sign up to set email alerts
|

Design and Medical Effects of a Vaginal Cleaning Device Generating Plasma-Activated Water with Antimicrobial Activity on Bacterial Vaginosis

Abstract: Bacterial vaginosis is a common female disease caused by a vaginal infection due to an overgrowth of bacteria that naturally live in the vaginal tract. Bacterial vaginosis has frequently been treated with the oral or vaginal administration of antibiotics and topical disinfectants. However, hygienic application of topical treatment deep in the vagina remains difficult. Herein, we introduce a novel vaginal cleaning device using plasma-activated water generated from supplied water. Remarkably, plasma source gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 22 publications
2
5
0
Order By: Relevance
“…If it is similar to the effect of betaine, and plasma-activated water spraying can replace the chemical betadine, it is believed that it has great advantages in treating patients with vaginitis. This finding is consistent with vaginal cleaning effect of PAW to patients (five patients) with bacterial vaginosis in a previous preliminary study [26]. In addition to the vaginal cleaning effect, the antibacterial effect of PAW on overgrown bacteria related to bacterial vaginosis could be expected, because numerous studies have shown the antibacterial effect of PAW [14][15][16][17].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…If it is similar to the effect of betaine, and plasma-activated water spraying can replace the chemical betadine, it is believed that it has great advantages in treating patients with vaginitis. This finding is consistent with vaginal cleaning effect of PAW to patients (five patients) with bacterial vaginosis in a previous preliminary study [26]. In addition to the vaginal cleaning effect, the antibacterial effect of PAW on overgrown bacteria related to bacterial vaginosis could be expected, because numerous studies have shown the antibacterial effect of PAW [14][15][16][17].…”
Section: Discussionsupporting
confidence: 91%
“…In this regard, plasma discharge in water would be a promising technology for easily and safely disinfecting tap water. In a previous preliminary study, we found a potential of PAW to patients with bacterial vaginosis (5 patients) [26]. However, there are still few studies related to the bacterial vaginosis of PAW when compared to the numerous studies showing the antibacterial effect of PAW.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…In previous studies, we confirmed the bactericidal effect of PAWs on clinically abnormal vaginal microbiota in clinical practice [14,19,20]. Patients sprayed with PAW (22.3%) had fewer Gram-positive and -negative bacteria than betadine treatment (BT) patients (14.4%) [14].…”
Section: Introductionsupporting
confidence: 78%
“…The PAW system comprised an underwater plasma-generating device, with plasma generated using procedures established previously [20]. An illustration of the device is provided in Figure 1; the device comprises a 3 L cleaning solution container, the atmospheric plasma electrodes, and a controller.…”
Section: Paw Generating System and Paw Processingmentioning
confidence: 99%